Analisis Kesetaraan Gender dalam Rumah Tangga Keluarga Modern dalam Penerapan di Lingkungan Pasutri (Pengantin yang Menikah Mudah) - Elisabeth Henderika Dua Neang; Trisnawati Bura; Fathia Aulia Mutmainnah; Anastasia Yuanti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the roots of the source of debate and differences of opinion about the reality of patriarchal family relationship patterns that dichotomize the roles of men (husbands) and women (wives) in the household, where the husband is the head of the family (public) and the wife is the housewife (domestic). The purpose of the study was to determine gender equality in modern family households in the application of the married couple environment (young brides and grooms, This research method uses a qualitative approach with a descriptive research type., The results of the study in the form of a dichotomous family relationship pattern, resulting in injustice and gender inequality. This condition certainly requires the construction of a relationship pattern based on justice and gender equality, so that a gender partnership is realized towards a harmonious family. The construction of a gender relationship pattern that is just and gender equal, is realized if there is cooperation and equal and fair division of roles between husband and wife, which refers to the planning and implementation of family resource management, so that family members have a division of roles in various activities (domestic, public, and community).